2019
DOI: 10.1111/cdev.13227
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Motor Competences in Predicting Working Memory Maintenance and Preparatory Processing

Abstract: The purpose of the study was the examination of the longitudinal association between motor competences and changes in preparatory processing during a task requiring working memory maintenance. At baseline, 52 Caucasian children aged 10-12 years completed the MOBAK-5 test battery and a Sternberg task, whereas the cue-P300 and the initial contingent negative variation (iCNV) were recorded via electroencephalography. After 9 months, the Sternberg task was administered again to assess changes in these neurophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 75 publications
(116 reference statements)
1
24
0
Order By: Relevance
“…Adolescents with higher physical activity could be prioritizing the anticipation for upcoming information, as was hinted also by the stronger cueing effect. Similar results were obtained in a longitudinal study measuring the association of preadolescent children's motor competences with working memory maintenance and neurophysiological measures of task preparation during 9 months (Ludyga et al, 2020). Ludyga et al, (2020) described a more effective utilization of the cue-relevant information by an increase in the cue-P300 amplitude during the task preparation stage in a Stenberg paradigm (used to assess working memory capacity) in children with high motor competences, thus supporting our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Adolescents with higher physical activity could be prioritizing the anticipation for upcoming information, as was hinted also by the stronger cueing effect. Similar results were obtained in a longitudinal study measuring the association of preadolescent children's motor competences with working memory maintenance and neurophysiological measures of task preparation during 9 months (Ludyga et al, 2020). Ludyga et al, (2020) described a more effective utilization of the cue-relevant information by an increase in the cue-P300 amplitude during the task preparation stage in a Stenberg paradigm (used to assess working memory capacity) in children with high motor competences, thus supporting our findings.…”
Section: Discussionsupporting
confidence: 91%
“…The cost-benefit effect of relying on the cue could also arise due to shared neural resources between selective attention and working memory (For a review see Gazzaley and Nobre, 2012). Physical activity has been associated with increased working memory capacity in children and adults (Alvarez-Bueno et al, 2017;Kamijo et al, 2011;Ludyga et al, 2020). In a task requiring both, working memory (holding the side of the target in memory) and possible attentional switching, the strategy relying on working memory may limit the resources for adaptive attentional switching.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some support for the relationship between motor skills and VSWM-related brain activity. Using EEG, Ludyga et al (2019) showed in a longitudinal study with 52 children, aged 8-10 years, that better motor skills at baseline were related to better attentional and preparatory processes during a working memory task 9 months later. This was mainly expressed in the premotor and motor cortex and in the frontoparietal network.…”
Section: Gross Motor Skills and Visuospatial Working Memorymentioning
confidence: 99%
“…Strengths of this study include the large sample of typically developing children that was examined. Previous studies on the relationships between physical fitness variables and brain functioning used sample sizes varying from 36-52 children (Chaddock et al, 2012;Voss et al, 2011;Ludyga et al, 2018Ludyga et al, , 2019. We analyzed data from 80 children.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation